2012
DOI: 10.1039/c2cc18053g
|View full text |Cite
|
Sign up to set email alerts
|

A facile synthesis of cubic (Im3̄m) alumina films on glass with potential catalytic activity

Abstract: Thermally stable phase pure mesoporous cubic (Im3m) alumina films were synthesized on glass substrates under ambient conditions. These cubic alumina films incorporated with Au NPs exhibited excellent catalytic property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…2. We have reported that pure alumina film (AlCe 0 ) possesses Im 3m mesopores in presence of F127 [26]. The XRD pattern of AlCe 0 film heated at 400°C revealed three peaks with d-values 11.1, 7.99 and 4.8 nm corresponding to the (1 1 0), (2 0 0) and (2 2 2) reflections, respectively ( Fig.…”
Section: Low Angle Xrd Studiesmentioning
confidence: 94%
See 4 more Smart Citations
“…2. We have reported that pure alumina film (AlCe 0 ) possesses Im 3m mesopores in presence of F127 [26]. The XRD pattern of AlCe 0 film heated at 400°C revealed three peaks with d-values 11.1, 7.99 and 4.8 nm corresponding to the (1 1 0), (2 0 0) and (2 2 2) reflections, respectively ( Fig.…”
Section: Low Angle Xrd Studiesmentioning
confidence: 94%
“…The XRD pattern of AlCe 0 film heated at 400°C revealed three peaks with d-values 11.1, 7.99 and 4.8 nm corresponding to the (1 1 0), (2 0 0) and (2 2 2) reflections, respectively ( Fig. 2a) [26]. The AlCe 1 film in Fig.…”
Section: Low Angle Xrd Studiesmentioning
confidence: 98%
See 3 more Smart Citations